At-risk adolescents as experts in a new requirements elicitation procedure for the development of a smart phone psychoeducational trauma-informed care application. (2nd January 2017) - Sockolow, Paulina; Schug, Seran; Zhu, Jichen; Smith, TJ; Senathirajah, Yalini; Bloom, Sandra
ABSTRACT: Background/Purpose : Adolescents from urban, socioeconomically disadvantaged communities of color encounter high rates of adverse childhood experiences. To address the resulting multidimensional problems, we developed an innovative approach, Experiential Participatory and Interactive Knowledge Elicitation (EPIKE), using remote experiential needs elicitation methods to generate design and content requirements for a mobile health (mHealth) psychoeducational intervention. Methods : At a community-based organization in a northeastern city, the research team developed EPIKE by incorporating elicitation of input on the graphics and conducting remotely recorded experiential meetings and iterative reviews of the design to produce an mHealth smartphone story application (app) prototype for the participants to critique. The 22 participants were 13- to 17-year-olds, predominantly African American and female, from underresourced communities. Results : The four goals of the design process were attained: 1) story development from participant input; 2) needs-elicitation that reflected the patient-centered care approach; 3) interactive story game creation that accommodates the participants' emotional and cognitive developmental needs; 4) development of a game that adolescents can relate to and that which matches their comfort levels of emotional intensity. Conclusions : The EPIKE approach can be used successfully to identify the needs of adolescents across the digital divide to inform the design and development of mHealth apps.